New bioactive Pt(II) binary and ternary metal complexes with guaifenesin drug: Synthesis, geometrical structure, and spectroscopic and thermal characterization. (13th September 2016) - Mahmoud, Walaa H.; Mohamed, Gehad G.; Mahmoud, Nessma F.
Abstract : Three new binary and ternary metal complexes of Pt(II) with guaifenesin (GFS) drug have been prepared by chelation to guaifenesin ligand (as primary ligand) and glycine amino acid (HGly) and 1, 10‐phenanthroline (1, 10‐Phen) (as secondary ligands). Characterization was conducted based on elemental analysis, molar conductance, infrared (IR) spectroscopy, thermogravimetric analysis and X‐ray diffraction. The complexes were found to have the formulae [Pt(GFS)2 ]⋅3H2 O (1 ), [Pt(GFS)2 (Gly)]Cl⋅H2 O (2 ) and [Pt(GFS)2 (Phen)]Cl2 (3 ). Magnetic and spectroscopic data revealed complexes1 –3 to have octahedral geometry. IR spectra suggested that GFS ligand coordinated in mononegative tridentate mode (OOO) for1 but in neutral bidentate mode (OO) for2 and3 . In addition, HGly behaves as mononegative bidentate coordinated to Pt(II) metal via deprotonated carboxylate O and amino group. IR data also evidenced the bidentate nature of 1, 10‐Phen ligand. The molecular and electronic structure of Pt(II) complex1 was optimized theoretically and the quantum chemical parameters were calculated. Complexes1 –3 were screened for their antibacterial activity on Gram‐positive bacteria ( Bacillus subtilis and Staphylococcus aureus ) and Gram‐negative bacteria ( Escherichia coli and Neisseria gonorrhoeae ) and for their in vitro antifungal activity against Candida albicans . The three Pt(II) complexes showed remarkable biological and cytotoxic activity. The chelates were also screened for their in vitro anticancer activity against the MFC7 breast cell line. Complex3 showed the highest activity with a low IC50 value of 3.38 μg ml −1 . Abstract : The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of Pt(II) complex [Pt(GFS)2 ]⋅3H2 O.